PENGARUH PENDIDIKAN PENGARUH PENDIDIKAN, PENGETAHUAN DAN PENYULUHAN KESEHATAN TERHADAP PENURUNAN GLUKOSA DARAH PADA PASIEN DM TIPE 2 DIPUSKESMAS PAKUHAJI KABUPATEN TANGERANG: Penurunan glukosa darah, pengaruh pendidikan, pengetahuan dan penyuluhan kesehatan - Farida, Ida; Sentosa, Bambang Mardi; Hapsah, Siti (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
ABSRACT Background: According to WHO, diabetes mellitus is a degenerative disease that is experienced by many Indonesians, and its prevalence continues to increase from year to year along with its complications. Good knowledge of disease is a provision as the basis for the application of health behavior of DM patients in managing themselves to achieve a better quality of life. Health education has a goal to change behavior starting from changes in education and knowledge. Purpose: To determine the effect of education, knowledge and health education on reducing blood glucose in type 2 DM patients at the Pakuhaji Public Health Center, Tangerang Regency. Research method: : this research used quantitative causal with a cross sectional approach, the technique used is sampling jenuh as many as 65 respondents. Result of the research: Based on the results of the T test, the effect of education has no effect on the decrease in blood glucose, knowledge has an effect on the decrease in blood glucose, and counseling has an effect on the decrease in blood glucose. Based on the results of the F test, the effect of education, knowledge and health education on the decrease in blood glucose results in F table 2.36 with a sig value of 0.000. Conclusion: The results showed that there was an effect of education, knowledge and health education on reducing blood glucose.